ETHNO-DEMOGRAPHIC CHANGES AND (GEO)POLITICAL CONSEQUENCES: The Case of a Request for the Territorial Autonomy of the Hungarian National Minority in the North of Serbia (2008-2013) - Budimir, Željko; Vuković, Nebojša (Politeia, 2019)
In this paper, the aspiration of the Hungarian national minority in northern Serbia (Vojvodina) towards the establishment of the Hungarian Regional Autonomy from 2008 to 2013 and the possible motives of such a request are analyzed. The paper’s fundamental thesis is indicative of the fact that the main cause for such a request is a rather observable depopulation trend in the Hungarian community, i.e. the reduction in the Hungarian community’s percentage share in the population of the Republic of Serbia and its northern province of Vojvodina. Strategies of the action of the political parties of the Hungarian national minority, directed towards the realisation of the idea of the Hungarian autonomous region are also demonstrated.
Keywords: Demography; regional autonomy; the Hungarians; minorities; Serbia